Lipid biomarker estimates of seasonal variations of aerosol organic carbon sources in coastal Qingdao, China. (January 2021) - Chen, Qu; Guo, Zhigang; Yu, Meng; Sachs, Julian P.; Hou, Pengfei; Li, Li; Jin, Gui'e; Liu, Yueying; Zhao, Meixun
Highlights: Seasonal OC sources at coastal city of Qingdao quantified with lipid biomarkers. Season and air mass trajectory determine aerosol load and OC composition. OC from coal-burning and continental dust 7-fold higher in cold than warm season. Marine-derived OC contribution is 1.4-fold higher in warm than cold season. Abstract: Aerosols represent a significant source of organic carbon (OC) to China's marginal seas, but their provenance and chemical composition remain understudied. At the boundary of the East Asian continent and China's marginal seas, the coastal city of Qingdao is well-situated to study the sources and seasonal variations of organic aerosols and their contribution to marginal seas. Twenty-nine aerosol samples collected in 2015–2016 were analyzed for total OC (TOC), n -alkanes (C17 –C33 ), n -alkanols (C20 –C32 ) and n -fatty acids ( n -FAs, C14 –C32 ). Concentrations of TOC (5.7–18 μg/m 3 ), n -alkanes (17.5–143 ng/m 3 ), n -alkanols (18–41 ng/m 3 ) and n -FAs (99.3–160 ng/m 3 ) were highest in winter when total aerosol concentrations were highest. Organic carbon-normalized (OC-normalized) biomarker concentrations were used to apportion different sources of aerosol OC: short- and mid-chain n -alkanes (26 ) for fossil fuel residues; long-chain n -alkanes (≥C26 ), mid- and long-chain n -alkanols (≥C20 ) and mid- and long-chain n -FAs (≥C20 ) for terrestrial plant OC; short-chain n -FAs (20 ) for marine OC. From these we inferred higher fossil fuel OC contributions during cold seasons when aerosols were mainly transported to Qingdao by continental air masses, higher terrestrial plant OC contributions during warm seasons when terrestrial plant productivity was at its peak, and higher marine OC contributions in warm seasons when marine air masses were transported to Qingdao. Comparing these results with those from other continental and marine locations demonstrates the utility of this biomarker approach in providing semi-quantitative estimates of temporal and spatial variations in the sources of organic aerosols at the land-sea interface of marginal seas, where carbon burial rates tend to be high.